Effectiveness of capsaicin nanoparticle gel of Capsicum frutescens L. on oral squamous cell carcinoma in Rattus norvegicus - Fitri Aniowati; Cantika Nadrotan Naim; Nova Dwi Anggraeni; Pratiwi Nur Widyaningsih (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: Oral squamous cell carcinoma (OSCC) is an oral cancer with a low life expectancy, less than five years after diagnosis. The drug therapy often used for OSCC patients is cisplatin, but it is considered to cause tumour persistence, drug resistance, and high toxicity. Therefore, it is important to test the development of alternative drugs from natural ingredients. One potential ingredient is green chilli pepper (Capsicum frutescens L.). It contains capsaicin that functions as an anticancer agent by suppressing BCa tumorigenesis so that proliferation is inhibited, as well as increasing and preventing p53 antibody mutations that play a role in cancer cell apoptosis. Purpose: This study aimed to compare effectiveness using capsaicin nanoparticle gel from green chilli pepper extract levels of 1% and 3.3% to reduce OSCC nodules. Methods: This study used 20 Rattus norvegicus that were randomly divided into five groups; C- (rat without treatment), C+ (rat induced to 7,12-Dimethylbenz(a)anthracene (DMBA)), E1 (DMBA exposed and given cisplatin, E2 (rat induced to DMBA and capsaicin extract nanoparticle gel with a concentration of 1%), and E3 (rat induced to DMBA and capsaicin extract nanoparticle gel with a concentration of 3.3%). The data were analysed statistically with the one-way ANOVA and least significance difference (LSD) test. Results: The comparison of mean nodule volume between C+ (5.834 ± 2.77 mm3) with E1 (1.75 ± 0.37 mm3), E2 (1.747 ± 0.36 mm3), and E3 (1.812 ± 0.11 mm3) had a significant difference (p = 0.00, p ≤ 0.05). Conclusion: Capsaicin nanoparticle gel with green chilli pepper extract at levels of 1% (E2) reduces OSCC nodules by more than gel with green chilli pepper extract at 3.3% (E3) concentration.